Dentists' willingness to screen for cardiovascular disease in the dental care setting: Findings from a nationally representative survey. Issue 4 (25th March 2019) - Singer, Richard H.; Feaster, Daniel J.; Stoutenberg, Mark; Hlaing, WayWay M.; Pereyra, Margaret; Abel, Stephen; Pollack, Harold; Gellman, Marc D.; Schneiderman, Neil; Metsch, Lisa R.
Abstract: Objective: Dental clinics offer an untapped health care setting to expand access to screening and early identification of cardiovascular disease (CVD) risk. This study examined the correlates of dentists' willingness to provide CVD screening in the dental care setting. Methods: Private practice and public health general dentists in the U.S. participated in a nationally representative survey from 2010 to 2011. The survey examined dentists' willingness to provide a finger stick test to support CVD screening and agreement that their professional role should include CVD screening. Results: Data analysed from 1802 respondents indicated that 46.6% of dentists were willing to provide CVD screening. The adjusted odds ratio (AOR) of dentists' willingness to screen for CVD was associated with currently screening for hypertension (AOR = 1.49, 95% CI 1.01, 2.20), screening for obesity (AOR = 1.66, 95% CI 1.17, 2.36) and agreement that their role as health care professionals includes CVD screening (AOR = 3.03, 95% CI 2.15, 4.29). Dentists' agreement that their role includes CVD screening was associated with self‐rated knowledge of CVD (good vs none or limited) and CVD training during their professional education (5 to 8 hours of training vs none or limited), (AOR = 5.75, 95% CI 2.26, 14.62) and (AOR = 3.84, 95% CI 2.17, 6.80), respectively. Conclusions: Our study highlights strategies that may be employed to expand future access to early detection of CVD risk. Including CVD screening instruction and clinical screening experiences in dental school curriculum may serve as catalysts to reshape the future scope of dental practice.